INVESTIGATION OF THE IMPACT OF DIFFERENT PARAMETERS ON THE MORPHOLOGY OF ELECTROSPUN POLYURETHANE NANOFIBERS - Fatima T. Sabri; Manaf A. Mahammed (Science Journal of University of Zakho, 2024)
In this research, nonwoven nanofiber mats were prepared using the electrospinning method for the solution of polyurethane polymer dissolved in acetic acid. Effects of solution concentration, solution flow rate, as well as high voltage on the morphonology and wettability of the prepared nanofibers were studied. Nanofiber morphology was investigated through the analysis of scanning electron microscopy (SEM) micrographs using ImageJ software, while the wettability of the nanofiber mat surfaces was studied through the measurement of the contact angle. Results revealed that when the concentration of the solution was changed from 8wt% to 12wt%, the average nanofiber diameter showed a significant increase from 0.326 µm to 0.380 µm, while the contact angle increased from 39 degrees to 79 degrees. Results also showed that when the applied high voltage was changed from 10 KV to 25 KV, the average nanofiber diameter decreased and then increased within the range of 0.380 to 0.497 µm and that the contact angle was increased from 81 degrees to 108 degrees showing an obvious switching from hydrophilic towards hydrophobic surface. When the syringe pump flow rate was changed from 0.012 ml/min to 0.02 ml/min, morphology measurements showed that the average nanofiber diameter showed a significant increase from 0.351 µm to 0.456 µm, and the surface contact angle was also increased from 43 degrees to 98 degrees. Finally, the results of Fourier Transform Infrared Spectroscopy (FTIR) and X-ray diffraction analysis (XRD) tests showed that the electrospun polyurethane polymer material used in this work was not changed during the electrospinning process.